Analisis Ekowisata Kreatif terhadap Peningkatan Ekonomi dan Pengentasan Kemiskinan di Kabupaten Langkat - Diwayana Putri Nasution (STIE Jambatan Bulan, 2022)
This study aims to analyze creative variables on Economic Improvement and Poverty Alleviation in Langkat Regency through intervention variables. Based on the results of the study, it is known that ecotourism has a significant effect on poverty alleviation, but not through increasing the economy as an intervention variable. In conclusion, economic improvement does not work as an intervention variable. The creative economy has a significant effect on reducing poverty indirectly, through increasing the economy as an intervening variable. The conclusion is that Economic Improvement is an intervention variable on the Creative Economy variable in alleviating poverty.